Strategi Quantum Teaching untuk Meningkatkan Minat Belajar IPA Siswa Kelas IV di SDI Duarato - Isidorus Yunus Mali; Yustrivat Asa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine the increase in interest in learning for fourth grade students in science subjects with the topic of discussing the characteristics of plants on Ceremai trees through the Quantum Teaching Learning Model at SDI Duarato for the 2024/2025 academic year. This type of research is Classroom Action Research (CAR). The subjects of this research were 15 grade IV students at SD Inpres Duarato, consisting of 8 male students and 7 female students. The object of this research is Natural Sciences (IPA) learning using the Quantum Teaching learning model. Based on research and data analysis, it can be concluded that the Quantum Teaching learning model can increase interest in learning science in class IV students at SD Inpres Duarato for the 2024/2025 academic year. This can be seen before implementing the Quantum Teaching learning model in science learning. Of the 15 students, 6 students (40%) completed it, and 9 students (60%) did not complete it. Furthermore, by applying the Quantum Teaching learning model, it was obtained that 9 students (60%) had completed their learning interest in cycle I, while 6 students (40%) had not completed it. In cycle II, 13 students (86.66%) completed it, and 2 students (13.33%) did not complete it. From the data above, there was an increase from the initial data, cycle I and cycle II.